The The relationship between “Sexual capital”, “Religiosity” and “University girls' Makeup” in Kurdistan Region: A field research in public and private universities in Erbil - Muhammad, Faez I. (Humanities Journal of University of Zakho, 2024)
This research was conducted with the aim of investigating the relationship between sexual capital, religiosity, and makeup of university girls in the Kurdistan region and how they affect each other. Since the type of research is "quantitative", it is based on the "survey method" and "questionnaire". The sampling method in this research was "stratified random sampling". The questionnaire was distributed among 402 female students in Erbil public and private universities, and SPSS and SmartPLS software was used for data analysis. The results of the research indicate that there is a direct relationship between "sexual capital" derived from Catherine Hakim's theory and "university girls' makeup" in the Kurdistan region. The type of Correlation and the effect of these two variables with "religiosity" are opposite and negative. After linking the "Makeup" variable with the demographic variables and placing them in the linear regression model, it was found that daily "exercise" and "study" have an inverse Correlation, while "social status" and "economic status" have a direct Correlation.